Pengaruh Perekonomian Keluarga terhadap Penggunaan BPJS Kesehatan Desa Cileles Jatinangor - Anisa Nurfiani; Estro Dariatno Sihaloho (Universitas Batanghari Jambi, 2019)
This study aims to determine whether or not there is a family economic relationship to the use of Cileles Jatinangor Village Health BPJS. Factors that are influenced by the family economy include, the average family income per month, number of family dependents, monthly BPJS Health installments, how often each family goes to health facilities in the past month, and how many times the use of BPJS Health by each family in the past month. The study was conducted by direct observation of each family in Cileles Jatinangor Village. This study took data as much as 60 samples of the family of Cileles Jatinangor Village. In this study the type of data used is Cross Section Data, meaning that the data obtained is data that is obtained only in one time and has many objects or samples. The data obtained will be processed using stata14 which is quantitative data and followed by simple regression using the OLS (Ordinary Least Square) approach. The results and discussion show that the variables have a negative correlation, the number of dependents has a negative correlation, the cost of BPJS has a positive correlation, the check up has a positive correlation, the use of BPJS has a positive correlation, and all variables are significant at the level of 10%.